2015
DOI: 10.1007/978-3-319-14595-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Enzymes in Halophilic Bacteria, Properties and Biotechnological Potential

Abstract: Halophilic bacteria are one of the most important extremophilic microorganisms that can be found in saline or hypersaline environments which are widely distributed around the world. They are not only adapted to live in saline environments in where other organisms are not able to thrive and grow, but also subjected to other kinds of extreme conditions, like high pH values, high or low temperature, low oxygen availability, pressure, and toxic metals. Because of these abilities, biodiversity and biotechnological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…The optimal stability and activity of haloenzymes commonly take place at a higher NaCl level and NaCl is needed to manage the structure. However, higher salt level hinders the presence of water in the microenvironment of the protein, thereby causing modifications in the structural and functional role of the enzyme . On the other hand, requirements for magnesium salts are broad among halotolerant and halophilic microorganisms; Mg 2+ is generally required in higher concentrations for growth.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal stability and activity of haloenzymes commonly take place at a higher NaCl level and NaCl is needed to manage the structure. However, higher salt level hinders the presence of water in the microenvironment of the protein, thereby causing modifications in the structural and functional role of the enzyme . On the other hand, requirements for magnesium salts are broad among halotolerant and halophilic microorganisms; Mg 2+ is generally required in higher concentrations for growth.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weight of these proteases was approximately 60 kDa, 45 kDa, and 35 kDa. In this regard, other studies on proteases from halophilic bacteria reported molecular mass values between 19 and 120 kDa [45]. To confirm the inhibition of the proteolytic activity, casein zymogram was performed in the presence of the aforementioned inhibitors (Fig.…”
Section: Characterization Of Extracellular Proteasesmentioning
confidence: 96%
“…This genus grows under low and high salinity and on various carbon sources ( 3 , 4 ) and even utilizes ectoine as the sole carbon and nitrogen source ( 5 ). In addition, strains of this genus have shown the ability to produce hydrolytic enzymes ( 6 8 ). For this reason, our research group studied the hydrolytic capacity of strain BLLS135, which showed great metabolic diversity associated with the production of this type of enzyme and the response to different types of stress.…”
Section: Announcementmentioning
confidence: 99%